A. E. Housman - Page, Norman. author. aut Link
XV, 236 p.
Keywords: A.E. Housman (1859-1936) was a poet of enormous popularity and widespread influence: a Latin scholar of the front rank, a superb prose stylist, a notable writer of comic verse and, thanks to the enormous success of A Shropshire Lad, one of the greatest and best-known poems in the English language, he became a legend in his own lifetime. Reissued to mark the centenary of the publication of A Shropshire Lad, Norman Page's highly-acclaimed biography is regarded as the most complete account of Housman's life and career available. Drawing on a wide range of sources, including much unpublished material, Norman Page provides us with a fascinating insight into Housman the poet, the scholar and the man. `By far the best biography of Housman we have ...' - Andrew Motion, Times Literary Supplement.